Comparison of Arabic Language Textbooks for Grade Five MI Published by the Ministry of Religion in 2020 With Books by Agus Wahyudi Based on BSNP Criteria - Hermawan, Acep; Fauzy, Akbar Nur (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study compares the quality of two Arabic textbooks for fifth-grade students in Madrasah Ibtidaiyah (MI), namely the textbook published by the Ministry of Religious Affairs (Kemenag) in 2020 and by Agus Wahyudi. The comparison is based on the criteria set by the National Education Standards Agency (BSNP). The background of this research is the importance of textbooks as the primary learning media, which must meet specific standards to ensure effective teaching and learning of Arabic in line with the curriculum. The research uses a descriptive qualitative method with document analysis techniques. Both textbooks are analyzed based on four critical aspects of the BSNP standards: content feasibility, presentation, language, and graphic design. Each element is evaluated to determine how well the two textbooks meet the required criteria. The results show that the Kemenag-published textbook is superior in content feasibility and presentation, offering a more systematic approach that aligns with the needs of MI students. Meanwhile, Agus Wahyudi’s textbook stands out in terms of graphic design and more straightforward language, making it easier for students to understand. However, both books require improvement in several areas to fully comply with BSNP standards. This study contributes to the comparative analysis of Arabic textbooks at the elementary level, a relatively underexplored area. Future research is recommended to delve deeper into the effectiveness of these textbooks in the classroom and to expand the scope to other educational levels for a more comprehensive understanding of Arabic textbook quality in Indonesia.